Adsorption of Indigo Carmen Dye by Using Corn Leaves as Natural Adsorbent Material - Fadhil, Omar H. Fadhil H.; Eisa, Mohammed Y.; Salih, Dina Abdalrahman; Nafeaa, Ziad R. (Al-Khwarizmi Engineering Journal, 2021)
In this paper, the ability of using corn leaves as low-cost natural biowaste adsorbent material for the removal of Indigo Carmen (IC) dye was studied. Batch mode system was used to study several parameters such as, contact time (4 days), concentration of dye (10-50) ppm, adsorbent dosage (0.05-0.25) gram, pH (2-12) and temperature (30-60) oC. The corn leaf was characterized by Fourier-transform infrared spectroscopy device before and after the adsorption process of the IC dye and scanning electron microscope device was used to find the morphology of the adsorbent material. The experimental data was imputing with several isotherms where it fits with Freundlich (R2 = 0.9937) and followed pseudo second order kinetic. The highest removal percent was equal to 91% of the dye which makes the corn leaves a suitable efficient material for the removal of IC dye from aqueous solutions.